DLK1 and DLK2, two non-canonical ligands of NOTCH receptors, differentially modulate the osteogenic differentiation of mesenchymal C3H10T1/2 cells - María-Milagros Rodríguez-Cano; María-Julia González-Gómez; Eva-María Monsalve; María-José M. Díaz-Guerra; Moustapha Kassem; Jorge Laborda; María-Luisa Nueda; Victoriano Baladrón (Biological Research)
Abstract Background C3H10T1/2 is a mesenchymal cell line capable of differentiating into osteoblasts, adipocytes and chondrocytes. The differentiation of these cells into osteoblasts is modulated by various transcription factors, such as RUNX2. Additionally, several interconnected signaling pathways, including the NOTCH pathway, play a crucial role in modulating their differentiation into mature bone cells. We have investigated the roles of DLK1 and DLK2, two non-canonical inhibitory ligands of NOTCH receptors, in the osteogenic differentiation of C3H10T1/2 cells. Results Our results corroborate existing evidence that DLK1 acts as an inhibitor of osteogenesis. In contrast, we demonstrate for the first time that DLK2 enhances this differentiation process. Additionally, our data suggest that NOTCH2, 3 and 4 receptors may promote osteogenesis, as indicated by their increased expression during this process, whereas NOTCH1 expression, which decreases during cell differentiation, might inhibit osteogenesis. Moreover, treatment with DAPT, a NOTCH signaling inhibitor, impeded osteogenic differentiation. We have confirmed the increase in ERK1/2 MAPK and p38 MAPK phosphorylation in C3H10T1/2 cells induced to differentiate to osteoblasts. Our new findings reveal increased ERK1/2 MAPK phosphorylation in differentiated C3H10T1/2 cells with a decrease in DLK1 expression or an overexpression of DLK2, which is coincident with the behavior of those transfectants where we have detected an increase in osteogenic differentiation. Additionally, p38 MAPK phosphorylation increases in differentiated C3H10T1/2 cells with reduced DLK1 levels. Conclusions Our results suggest that DLK1 may inhibit osteogenesis, while DLK2 may promote it, by modulating NOTCH signaling and the phosphorylation of ERK1/2 and p38 MAPK pathways. Given the established inhibitory effect of DLK proteins on NOTCH signaling, these new insights could pave the way for developing future therapeutic strategies aimed at treating bone diseases.